Community Healing and Resistance Through Storytelling: A Framework to Address Racial Trauma in Africana Communities. (March 2020) - Chioneso, Nkechinyelum A.; Hunter, Carla D.; Gobin, Robyn L.; McNeil Smith, Shardé; Mendenhall, Ruby; Neville, Helen A.
Racial trauma, an ongoing consequence of historical trauma, has deleterious effects on the well-being of Africana communities. The psychological literature primarily reflects individual processes in the relationship between racial trauma and healing. Going beyond individualistic approaches, we present a community healing framework informed by multidisciplinary scholarship: Community Healing and Resistance Through Storytelling ( C-HeARTS ). Three major components of the framework are delineated: (a) justice as both a condition of and an outcome of community healing; (b) culturally syntonic processes (i.e., storytelling and resistance) that direct the renarrating of trauma and act as conduits for transformation; and (c) psychological dimensions (i.e., connectedness, collective memory, and critical consciousness) that promote justice-informed outcomes. In the C-HeARTS framework, community is advanced as an agent of change while centering justice and the important role of cultural practices to facilitate community healing.